Hubungan Antara Pemakaian Alat Pelindung (Kondom) Dengan Ditemukannya Trichomonas Vaginalis Pada Wanita Pekerja Seks - Budiati, Srini; Haryatmi, Dwi (Jurnal Kesehatan, 2024)
Trichomoniasis is one of the sexually transmitted infectious diseases caused by Trichomonas vaginalis. It is transmitted through sexual intercourse. Women sex workers with a tendency to change partners are at high risk of contracting or transmitting this disease. The study aims to analyze the relationship between condom use and the discovery of T. vaginalis. The research is observational with a cross-sectional approach. The research sample used a total sampling technique, namely WPS (Wanita Pekerja Seks/ Women sex workers) on Krakal beach, Gunungkidul, totalling 40 people. The research data was obtained from microscopic observations of T. vaginalis and questionnaire results, which were then tested with chi-squares. Most sex workers who use condoms have a negative result of 19 (47.5%). The results showed that there was a significant relationship between condom use and the incidence of T. vaginalis infection, with a significant value of 0.003 (p-value < 0.05), which was smaller than the alpha value of 0.05 (5%). The use of safety devices (condoms) in risky sexual activities is a strategy to prevent the transmission of T. vaginalis infection.